Being a Nation State in the Twenty-First Century: Between State and Synagogue in Modern Israel - Fridman, Shuḳi (Judaism and Jewish Life, 2023)
Since the founding of the Zionist movement until today, the question of the relationship between “Church” and the state in Israel remains unresolved, resulting in a continuous legal and social conflict among Israelis. The tension that arises from Judaism acting not only as a religion and culture but also as a national entity constitutionally underpinning an entire state-resulting in the “Jewish and democratic state” of Israel-manifests in major aspects of daily life for Israelis, such as marriage and divorce, conversion, Shabbat. This book presents a crucial piece of scholarship in understanding the history behind and current dynamics of the relation between state and religion in Israel, and, in doing so, provides a unique perspective on future potential solutions to this social rift